Main results of the Russian trial «ALTAIR» - E. V. Shlyakhto; A. O. Conrady; Yu. V. Sviryaev (Кардиоваскулярная терапия и профилактика)
The results of the multi-center, open, titrating trial of rilmenidine «ALTAIR» (ALbarel: effectiveness and Tolerability in ArterIal hypeRtension) are demonstrated. Aim. To assess antihypertensive effectiveness and safety of rilmenidine as monotherapy and in combination with amlodipine in out-patients with mild to moderate arterial hypertension (AH), to investigate its effects on quality of life and treatment compliance. Material and methods. The study involved 677 patients: 610 participants (90.4%) completely fulfilled the protocol, and another 67 (9.6%) dropped out. Therapy lasted for 16 weeks. Clinical visits were performed at Week 4, 8, 12 and 16 of the treatment. Results. Rilmenidine (1-2 mg/d) therapy in Stage I-II AH was associated with BP target level achievement in 46.6% of the cases, with good therapy tolerability. Adverse events were registered in 11.9% of the participants, but treatment discontinuation and study termination was necessary in 4.4% of the subjects only. Combination of rilmenidine and amlodipine (2.5-5 mg/d) resulted in responder percentage increase to 87.5%, with simultaneous increase in adverse event rates, though. Conclusion. ALTAIR trial results demonstrated high effectiveness and good tolerability of rilmenidine treatment, as monotherapy or in combination with amlodipine.